The Reconstruction of the Danubian Neolithic House and the Scientific Importance of Architectural Studies - Anick Coudart (EXARC, 2013)
In May 1987, the subcommittee on Archaeology of the European Science Foundation (ESF) organised a workshop on “the reconstruction of wooden buildings from the prehistoric and early historic period”. (...) The 1980s was the beginning of a boom in the construction of archaeologically inspired buildings inside and outside archaeological open-air centres. In their proposal to the ESF, they wrote of the problems of constructing at a 1:1 size. Some of the problems addressed are still valid today.